Analyzing Information Access using Functional and Non-Functional Models for Internet of Things (IoT) - K. Sakthidasan Sankaran, (Journal of Electronic Design Engineering, 2021)
The IoT is a growing technology is associated with various smart objects that give data interoperability for application purposes. The device that is accessed through the internet is done on a heterogeneous platform. It also handles things without considering the capability and it faces the problem of how the IoT technology accesses the internet. The primary step is modeling the semantic data used to store the IoT data that is interpreted. Then the features and attributes are recognized in a functional and non-functional way. The smart home is proposed, and they are communicating with an RFID tag. At last, the access in IoT is examined and concluded.